Evolution of the Design and Fabrication of Astrophysics Targets for Turbulent Dynamo (TDYNO) Experiments on OMEGA. (3rd April 2018) - Muller, S. A.; Kaczala, D. N.; Abu-Shawareb, H. M.; Alfonso, E. L.; Carlson, L. C.; Mauldin, M.; Fitzsimmons, P.; Lamb, D.; Tzeferacos, P.; Chen, L.; Gregori, G.; Rigby, A.; et al.
Abstract: Highly complex targets are constructed by General Atomics for astrophysically relevant experiments conducted by the University of Chicago on the OMEGA laser facility through the National Laser Users' Facility (NLUF) program. Several novel target components are fabricated, precision assembled, and extensively measured in support of this campaign and have evolved over the last 3 years to improve both the science and assembly. Examples include unique laser-machined polyimide grids to enhance plasma mixing at the target center, precision-micromachined cylindrical shields that also act as component spacers, drawn glass target supports to suspend physics packages at critical distances, and tilted pinholes for collimated proton radiography. Target component fabrication and evolution details for the NLUF Turbulent Dynamo (TDYNO) campaign are presented, along with precision-assembly techniques, metrology methods, and considerations for future TDYNO experiments on OMEGA.